Gaya Belajar Mahasiswa Farmasi dalam Pembelajaran Fisika Berdasarkan Indeks Learning Style Felder Silverman - Nasharuddin; Wahyuddin; Muhammad Amin Said; Hajra Yansa; Miftahul Janna; Andi Reski Amelia (Pendidikan Fisika UIN Alauddin Makassar, 2023)
Learning style is a vital component in improving the quality of learning in physics classes. This study identified the learning styles of pharmacy students in learning physics based on Felder Silverman's Learning Style Index (ILS) through a survey of first-year students. ILS Felder Silverman determines the 4 dimensions of learning style preferences, namely processing (active-reflective), perception (sensing-intuitive), input (visual-verbal), and understanding (sequential-global). Questionnaires were distributed using Google Forms in more than three weeks. The collected data were analyzed descriptively quantitatively through the ILS scoring sheet. The results showed that the preference for Active, Sensing, Visual, and Sequential (ASViS) learning styles was owned by pharmacy students in learning physics. ASViS is dominant at a balanced level, successively: Active (39.27%), Sensing (31.94%), Visual (35.08%) and Sequential (44.50%). The implications of this study illustrate the learning of lecturers in physics classes who should apply various methods by actively involving students through experiments, project-based learning and discussions and occasionally reflect in explaining material. Also apply convergent and divergent learning